HIV-1 pretreatment drug resistance in vertically infected children is associated with poor virological response to protease inhibitor (PI)-based first-line antiretroviral therapy (ART): results from a cohort study in Argentina. (5th May 2022) - Rozenszajn, Mijael; Arazi-Caillaud, Solange; Taicz, Moira; Bologna, Rosa; Mangano, Andrea; Aulicino, Paula C
Abstract: Background: Increasing evidence from adult cohorts suggests an important role of HIV-1 pretreatment drug resistance (PDR) in ART failure, in spite of treatment being fully active according to baseline genotyping tests. Whether this is also true for children is unknown. Methods: Virological and immunological parameters were longitudinally assessed in a group of 39 HIV-1 vertically infected children starting first-line lopinavir/ritonavir-based ART at a median of 5.0 months (IQR = 3.0–9.0). Evolution of viral load (VL) over time was compared between children with and without baseline PDR, as defined by the WHO mutation list. Results: Resistance-associated mutations (RAMs) in the HIV-1 pol gene were present in nine HIV-1-infected children (23%) before initiation of first-line ART (PDR group). Of them, six carried RAMs associated with NNRTIs (NNRTI-PDR subgroup). At 4–8 weeks after ART initiation, the proportion of children achieving ≥1 log VL reduction was 87% for the no-PDR group versus 33% and 16.7% for the PDR group and the NNRTI-PDR subgroup, respectively. During follow-up, children with no PDR reached virological suppression almost four times faster than children with PDR or NNRTI-PDR [no-PDR = 631 days and PDR = 2134 days ( P  = 0.1249) and NNRTI-PDR = 2134 days ( P  = 0.0447)]. CD4 T cells remained similar between the study groups over time. Conclusions: HIV-1 baseline genotyping at diagnosis in vertically infected children is important for improved personalized medicine. While the mechanism is unclear, cases with PDR (particularly to NNRTIs) require closer monitoring of their first-line ART regimens in order to avoid early virological failures and prevent further accumulation of resistance.